Vector-Like Quarks at the LHC: A unified perspective from ATLAS and CMS exclusion limits - R. Benbrik; M. Boukidi; M. Ech-chaouy; S. Moretti; K. Salime; Q. S. Yan (Journal of High Energy Physics)
Abstract In this work, we present a comprehensive review of the most up-to-date exclusion limits on Vector-Like Quarks (VLQs) derived from ATLAS and CMS data at the Large Hadron Collider (LHC). Our analysis encompasses both pair and single production modes, systematically comparing results from the two collaborations to identify and employ the most stringent bounds at each mass point. We evaluate the excluded parameter space for VLQs under singlet, doublet, and triplet representations. For top-like VLQs (T), the exclusion limits rule out masses up to 1.49 TeV in singlet scenarios, while single production constrains the mixing parameter κ to values below 0.26 at m T ~ 1.5 TeV and up to 0.42 for m T ~ 2 TeV. For bottom-like VLQs (B), the strongest exclusion limits from pair production exclude masses up to 1.52 TeV in doublet configurations, with single production constraining κ values between 0.2 and 0.7 depending on the mass. For exotic VLQs, such as X and Y, pair production excludes masses up to 1.46 TeV and 1.7 TeV, respectively. The constraints on κ from these analyses become increasingly restrictive at higher masses, reflecting the enhanced sensitivity of single production channels in this regime. For X, κ is constrained below 0.16 for masses between 0.8 and 1.6 TeV and further tightens to κ < 0.2 as the mass approaches 1.8 TeV. Similarly, for Y, κ values are constrained below 0.26 around m Y ~ 1.7 TeV, with exclusions gradually relaxing at higher masses. These exclusion regions, derived from the most stringent LHC search results, offer a unified and up-to-date perspective on VLQ phenomenology. The results were computed using VLQBounds, a new Python-based tool specifically developed for this purpose.